2018
DOI: 10.1097/rlu.0000000000002161
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Prostate-Specific Membrane Antigen Expression in Metastatic Differentiated Thyroid Cancer Using 68Ga-PSMA-HBED-CC PET/CT

Abstract: Ga-PSMA-HBED-CC PET/CT is a potentially useful imaging modality in patients of mDTC with most (70%) of PSMA expressing metastasis being localized to the bones. PSMA PET/CT could be useful for identifying patients with limited therapeutic options (eg, TENIS) who might benefit from PSMA-targeted radionuclide therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 12 publications
4
28
1
1
Order By: Relevance
“…This is in concordance with Taywade et al, Verma et al, and Lütje et al, who also detected these and various other lesions [14,15,19]. Furthermore, our results show 18 FDG PET/CT uptake in liver metastases, which was also shown in RAI-sensitive patients by Verma et al [15]. In addition, we found PSMA uptake in leptomeningeal metastases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in concordance with Taywade et al, Verma et al, and Lütje et al, who also detected these and various other lesions [14,15,19]. Furthermore, our results show 18 FDG PET/CT uptake in liver metastases, which was also shown in RAI-sensitive patients by Verma et al [15]. In addition, we found PSMA uptake in leptomeningeal metastases.…”
Section: Discussionsupporting
confidence: 93%
“…Altogether, PSMA is a potential target for theranostics in RAI-refractory DTC. Lütje et al and Verma et al found results suggesting that the use of 68 Ga-PSMA PET/CT in DTC is suitable for determining whether a RAI-refractory patient is eligible for PSMA-targeted therapies, such as treatment with Lu-PSMA-617 [14,15]. To investigate the value of the theranostic PSMA, we performed a single-center retrospective analysis on patients with RAI-refractory DTC, referred for 68 Ga-PSMA PET/CT to investigate suitability for peptide radioligand therapy with 177 Lu-PSMA-617.…”
Section: Introductionmentioning
confidence: 99%
“…They were referred for [ 68 Ga]Ga-PSMA-11 PET/CT on clinical indication to evaluate their eligibility for peptide radioligand therapy with [ 177 Lu]Lu-PSMA-617, since PSMA expression in DTC has been documented before. 13 As such, baseline PSMA PET/CT scan data for this patient group before 131 I-treatments do not exist. Any comparisons to a normal reference control are based on well-established data from literature.…”
Section: Methodsmentioning
confidence: 96%
“…Ein großes therapeutisches Potenzial, auch als Ersatz der Radiojod-Therapie bei Refraktärität, dürfte zukünftig dem Einsatz von 68 Ga-PSMA [11,12], und 68 Ga-FAPI [13] bzw. den entsprechenden therapeutischen Liganden zukommen.…”
Section: Bezug Zur Nuklearmedizinischen Diagnostik Und Therapie Der Sunclassified